Nutritional profiling and contaminant levels of five underutilized fish species in Norway - Kendler, Sophie; Thornes, Frida Walle; Jakobsen, Anita Nordeng; Lerfall, Jørgen (Frontiers in Nutrition, 2023)
Exploring and making use of little utilized marine resources (LUR) can be a sustainable approach to achieve future demands of fish consumption by the ever-growing population. Five LUR species, namely European plaice (Pleuronectes platessa), European flounder (Platichthys flesus), lemon sole (Microstomus kitt), megrim (Whiffiagonis lepidorhombus) and thornback ray (Raja clavate), often captured as by-catch in Norway, were characterized for their nutritional value and potential accumulation of hazardous components. The proximate composition, protein profile, fatty acid profile as well as essential and toxic trace elements and polychlorinated biphenyls (PCBs) were analysed. Digestible indispensable amino acid (DIAA) ratios and scores and contributions of omega-3 fatty acids to the diet were calculated. Analysis on proximate composition revealed low fat contents of 0.74 to 1.25% and sufficient protein contents between 16.9 to 24% in the five species. Results of DIAA indicate a profitable distribution, with contributions exceeding the daily intake recommendations for an adult person related to a 200 g fillet. Moreover, findings on the distribution of eicosapentaenoic (EPA) and docosahexaenoic acid (DHA) showed remarkable results, considering that the investigated species are lean fish. All five investigated fish exceed the recommended average daily intake level (AI) of EPA + DHA in a 200 g portion. As to toxic trace elements and PCBs, no significantly elevated levels were found considering a portion size of 200 g. Consequently, the nutritional quality of the investigated fish can be regarded as profitable with overall low potential health risks.